Ethics and financial reporting in the United States - Stewart, I. C. (Journal of business ethics, 1986)
The purpose of this paper is to describe briefly the institutional arrangements which condition the activities of accountants in the United States; to heighten an awareness of the values which are embodied in the existing structures of accountability; to appraise the consistency with which the established ideals of society have been actualised in financial reporting, and to discern the shape of the emerging history of financial reporting in the light of new values and possibilities. I suggest that the tradition of fair presentation in financial reporting is in danger of being eliminated by a purely political response to previous abuses. Mandatory accounting standards do have a role in preventing these abuses, but they can also be seen as instruments of distributive justice. To promote an awareness and discussion of the issues, I point out some of the goals and values underlying a few of the major structures designed for the distribution of economic costs and benefits.